Management of urban waters with nature-based solutions in circular cities—exemplified through seven urban circularity challenges - Oral, Hasan Volkan; Radinja, Matej; Rizzo, Anacleto; Kearney, Katharina; Andersen, Theis Raaschou; Krzeminski, Pawel; Buttiglieri, G. (MDPI, 2021)
Nature-Based Solutions (NBS) have been proven to effectively mitigate and solve resource depletion and climate-related challenges in urban areas. The COST (Cooperation in Science and Technology) Action CA17133 entitled “Implementing nature-based solutions (NBS) for building a resourceful circular city” has established seven urban circularity challenges (UCC) that can be addressed effectively with NBS. This paper presents the outcomes of five elucidation workshops with more than 20 European experts from different backgrounds. These international workshops were used to examine the effectiveness of NBS to address UCC and foster NBS implementation towards circular urban water management. A major outcome was the identification of the two most relevant challenges for water resources in urban areas: ‘Restoring and maintaining the water cycle’ (UCC1) and ‘Water and waste treatment, recovery, and reuse’ (UCC2). s Moreover, significant synergies with ‘Nutrient recovery and reuse’, ‘Material recovery and reuse’, ‘Food and biomass production’, ‘Energy efficiency and recovery’, and ‘Building system recovery’ were identified. Additionally, the paper presents real-life case studies to demonstrate how different NBS and supporting units can contribute to the UCC. Finally, a case-based semi-quantitative assessment of the presented NBS was performed. Most notably, this paper identifies the most typically employed NBS that enable processes for UCC1 and UCC2. While current consensus is well established by experts in individual NBS, we presently highlight the potential to address UCC by combining different NBS and synergize enabling processes. This study presents a new paradigm and aims to enhance awareness on the ability of NBS to solve multiple urban circularity issues. © 2021 Elsevier B.V., All rights reserved.
Keywords: Blue-green infrastructure; Climate change and mitigation; Sustainable water management; Urban circularity challenges; Water reuse